A vigilância na internet: a circulação midiática brasileira do vazamento de dados da NSA por Edward Snowden - Spaniol, Bruna Paiani Nasser (2015)
This research seeks to understand how the problem of information security is treated in Brazil by the public thematization and also how it can affect the political and economic aspects of both Brazilian companies and government by using a study case based on the document leak event of the National Security Agency by Snowden. For this, the study case of sites, blogs and news portal coverage was carried out from the perspective of evidential paradigm, studies of movement and event concept. We are interested in examining how the media handles the information security topic and what its impact on national and international political relations. The subject matter was considered the largest data leakage in history of the NSA, which ranks as the world's largest agency of expression intelligence. This leak caused great repercussions in Brazil since it was revealed that the country was the most watched by the United States of America, behind only USA itself. The consequences were: a big tension between Brazil and the US and a public discussion about privacy and freedom on Internet. The research analyzed 256 publications released by Brazilian media outlets in digital media, in the period between June and July 2013.